2013
DOI: 10.1038/ismej.2013.69
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic insights into strategies of carbon conservation and unusual sulfur biogeochemistry in a hypersaline Antarctic lake

Abstract: Organic Lake is a shallow, marine-derived hypersaline lake in the Vestfold Hills, Antarctica that has the highest reported concentration of dimethylsulfide (DMS) in a natural body of water. To determine the composition and functional potential of the microbial community and learn about the unusual sulfur chemistry in Organic Lake, shotgun metagenomics was performed on size-fractionated samples collected along a depth profile. Eucaryal phytoflagellates were the main photosynthetic organisms. Bacteria were domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 103 publications
3
57
0
Order By: Relevance
“…Ammonium reached the highest concentrations in the deep anoxic layers of the lakes, indicating a higher rate of mineralization than assimilation, coupled with a higher stability in the acidic pH range. The depth profiles of ammonium concentration were comparable for both Ursu and Fara Fund lakes, and similar to the ones described in other stratified lakes (Auguet et al, 2012;La Cono et al, 2013;Yau et al, 2013). The vertical profiles of nutrients (sulfate, sulfide, nitrite, nitrate and phosphate) were found to be a result of sedimentation, biogeochemical cycling or conservative mixing (Pasche et al, 2009), and were also comparable with those found in other studied lakes (Lepère et al, 2010;La Cono et al, 2013;Marteinsson et al, 2013).…”
Section: Water Chemistrysupporting
confidence: 86%
See 2 more Smart Citations
“…Ammonium reached the highest concentrations in the deep anoxic layers of the lakes, indicating a higher rate of mineralization than assimilation, coupled with a higher stability in the acidic pH range. The depth profiles of ammonium concentration were comparable for both Ursu and Fara Fund lakes, and similar to the ones described in other stratified lakes (Auguet et al, 2012;La Cono et al, 2013;Yau et al, 2013). The vertical profiles of nutrients (sulfate, sulfide, nitrite, nitrate and phosphate) were found to be a result of sedimentation, biogeochemical cycling or conservative mixing (Pasche et al, 2009), and were also comparable with those found in other studied lakes (Lepère et al, 2010;La Cono et al, 2013;Marteinsson et al, 2013).…”
Section: Water Chemistrysupporting
confidence: 86%
“…The relative abundance of Archaea in the 0.5 (~2%) and 2 m (1.2%) depth assemblages was minor, and could be attributed to the lower salinity levels found at these depths (that is,~70 g l − 1 ). Similar findings were reported in other saline lakes (Yau et al, 2013;Baricz et al, 2014) or shallow ponds (Ghai et al, 2011), and are supported by the fact that most haloarchaeal species lyse at salt concentrations of o100 g l − 1 (Andrei et al, 2012). As the salinity increased over 240 g l − 1 (at 3.5 m depth) the proportion of the Archaea in the communities was higher, ranging between~20% (at 3.5 m depth) and~40% (at 9 m depth), but nonetheless lower than the bacterial one.…”
Section: Vertical Patterns In Prokaryotic Abundancessupporting
confidence: 79%
See 1 more Smart Citation
“…For example, reactant pools may frequently be assimilated, leached or re-routed through other biochemical pathways independent of the pathway that corresponds to the gene of interest. The advent of relatively new technologies like gene microarrays (He et al, 2007) and metagenomics (Tyson et al, 2004;Mackelprang et al, 2011;Fierer et al, 2012;Yau et al, 2013) has allowed researchers to rapidly assess more genes compared with qPCR techniques. However, the use of enticing new technologies for assessing gene abundance is also susceptible to many of the same biases that obscure the links between molecular information and biogeochemical processes illustrated by the meta-analysis presented here.…”
Section: Does Gene Abundance Infer Process?mentioning
confidence: 99%
“…To evaluate these linkages, many studies use molecular techniques, including quantitative PCR (qPCR), reversetranscription qPCR (Liu et al, 2010;Shannon et al, 2011), microarrays (Taroncher-Oldenburg et al, 2003;Kang et al, 2013) and, most recently, metagenomics (Tyson et al, 2004;Mackelprang et al, 2011;Fierer et al, 2012;Yau et al, 2013). These techniques measure the relative abundances of nucleic acids encoding proteins that catalyze biogeochemical reactions, which we refer to as protein-encoding genes and transcripts (or henceforth as gene or transcript).…”
mentioning
confidence: 99%